1983
DOI: 10.1111/j.1346-8138.1983.tb01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Localization of 2,4‐dinitrophenyl Groups on Draining Lymph Node Cells of Guinea Pigs Following Skin Painting With 2,4‐dinitrochlorobenzene

Abstract: The distribution of DNP groups on cells taken from draining lymph nodes of guinea pigs 12 hours after painting the skin with DNCB was examined by scanning immunoelectron microscopy using antibody directed against DNP groups with bacteriophage T4 as a visual marker. The studies showed that DNP groups were distributed on the surface of the cells, demonstrating some differences in distribution pattern among the cells. The incidence of cells on which DNP groups were detected was approximately 60% in the normal ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Takei (17) reported that after oral dosing of DNCB, the DNP group was observed in the epithelial cells of the gastrointestinal mucosa, mesenteric lymph nodes, Peyer's patches, spleen and peripheral blood lymphocytic cells, a finding common to that obtained after epicutaneous dosing showing the presence of the DNP group at the site of application and in the regional lymph nodes, spleen and peripheral blood lymphocytic cells. Scanning immunoelectron microscopic studies of the distribution of epicutaneous DNCB in guinea pigs revealed that the DNP group was present on the surface of epidermal and lymphocytic cells, indicating that DNCB binds with components of the plasma membrane of these cells in vitro (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Takei (17) reported that after oral dosing of DNCB, the DNP group was observed in the epithelial cells of the gastrointestinal mucosa, mesenteric lymph nodes, Peyer's patches, spleen and peripheral blood lymphocytic cells, a finding common to that obtained after epicutaneous dosing showing the presence of the DNP group at the site of application and in the regional lymph nodes, spleen and peripheral blood lymphocytic cells. Scanning immunoelectron microscopic studies of the distribution of epicutaneous DNCB in guinea pigs revealed that the DNP group was present on the surface of epidermal and lymphocytic cells, indicating that DNCB binds with components of the plasma membrane of these cells in vitro (18,19).…”
Section: Discussionmentioning
confidence: 99%